(untitled) (Doctor Virtualis, 2025)
This study explores the role played by the potentia absoluta Dei, understood as an instrument for redefining metaphysical possibilities, in Ockham’s refutation of universals. First, several textual examples are analyzed in which the appeal to the potentia absoluta serves to unmask the illusory nature of superfluous entities. The Ockhamist critique, considering the world as a collection of singular things devoid of vertical ontological ties, prompts a comparative reading between the Franciscan’s commentary on Porphyry’s Isagoge and Umberto Eco’s essay L’Antiporfirio. Despite the indisputable difference between the two cultural paradigms, a fil rouge can be identified that unites the diversity of their polemical aims.